Antimicrobial properties of bio‐inspired poly(4‐vinyl‐2‐pyridone) and its N‐alkylated cationic derivatives. Issue 1 (13th September 2016) - Shandil, Yashwant; Chauhan, Ghanshyam S; Kumar, Pradeep
Abstract: Developing new antimicrobial polymers and designing new antimicrobial materials are important research areas for overcoming bacterial resistance. In the present study a new polymer, poly(4‐vinyl‐2‐pyridone), having bioactive structure analogous to that of naturally occurring heterocyclic compounds, was synthesized from 4‐vinylpyridine following a simple protocol. To augment the antibacterial properties of the synthesized polymer, N ‐alkylation of the heterocyclic pyridone moieties was achieved with ethylene chlorohydrin (2‐chloroethanol) to generate choline analogous structure. Also, its N ‐butylated analogue was synthesized as a reference compound to study structure–activity relationship. Structures of the polymers were confirmed using various characterization techniques. Antimicrobial efficacy of the polymers was determined using the minimum inhibitory concentration method in parallel experiments. The test microorganisms used were a Gram (+) bacterium ( Staphylococcus epidermidis ), Gram (−) bacteria ( Salmonella typhi, Pseudomonas aeruginosa and Escherichia coli ) and a fungus ( Candida albicans ). Both the polymer derivatives are far more effective antimicrobial agents than the pristine polymer. Trends in the antimicrobial efficacy of these polymers correlate with their zeta potential values. © 2016 Society of Chemical Industry Abstract : Antimicrobial polymers having 2‐pyridone structure and its N ‐alkylated form are reported for the first time, and antimicrobial efficacy was found to enhance appreciably after the alkylation process.